Ultrasonic Glasses for the Blind (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Ultrasonic Glasses for the Blind is a real-time wearable assistive system developed to improve the mobility and safety of visually impaired individuals through intelligent obstacle detection and voice-based navigation assistance. The system integrates an HC-SR04 ultrasonic sensor, Arduino Nano microcontroller, and ISD1820 voice module to continuously monitor surrounding obstacles and provide immediate audio alerts. Distance measurement is performed using ultrasonic echo-time calculation and processed using predefined threshold logic for real-time obstacle identification.The complete prototype is mounted on a lightweight spectacle frame and powered by a rechargeable lithium battery, ensuring portability and continuous operation for daily use. Experimental evaluation demonstrated an obstacle detection accuracy of 97%, an average response time of 150 ms, and an effective detection range of 2 cm to 400 cm, with continuous battery backup of 5 hours. The total implementation cost of approximately ₹1500 makes the proposed system affordable and accessible for practical deployment.Compared to conventional buzzer-based assistive devices, the proposed voice-alert mechanism offers clearer and more intuitive user guidance, improving usability and response efficiency. The experimental results confirm that the system provides a reliable, low-cost, and efficient embedded assistive technology solution that significantly enhances independent mobility and safety for visually impaired users.